Fakoemulsyfikacja zaćmy a ciśnienie wewnątrzgałkowe u chorych z jaskrą - Mierzejewski, Andrzej; Eliks, Iwona; Kałużny, Bartłomiej; Zygulska, Maja; Harasimowicz, Bartosz; Kałużny, Jakub (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the influence of recently performed cataract phacoemulsification in glaucomatous eyes on postoperative intraocular pressure (IOP). Material and methods: 100 eyes of 86 glaucoma patients who underwent cataract phacoemulsification with simultaneous intraocular lens implantation, were retrospectively analyzed. The patients were divided into two groups: I – 61 patients (71 eyes) with open angle glaucoma, and II – 25 patients (29 eyes) with angle closure glaucoma. Both groups were subdivided into two subgroups, depending on presence of symptoms of pseudoexfoliation (PEX) syndrome (A = with, and B = without symptoms of PEX syndrome). All patients were examined in the department where the surgeries were performed; before surgery, on the first day after the procedure, and again during the last follow-up examinations, 6 to 30 months after the procedure. Results: Before surgery, the intraocular pressure (IOP) was at mean value of 19.02 ± 4.55 mmHg in group I, and 20.01 ± 6.43 mmHg in group II. On the first day after surgery, the IOP was 17.42 ± 7.17 and 20.36 ± 8.98 mmHg, respectively. IOP exceeding 20 mmHg was found in 7 eyes in group I, and in 6 eyes in group II. During the last follow-up examinations the IOP was 14.59 ± 3.73 and 14.01 ± 4.50 mmHg, respectively, and was lower than measured before surgery, by an average of 4.43 mmHg in group I (P < 1 × 10-5), and 6.00 mmHg in group II (P < 1 × 10-4). In both groups, the reduction of IOP in patients with PEX was even more remarkable. The number of glaucoma medication necessary to control the pressure was reduced on average by 0.28 in group I, and 0.31 in group II. Conclusions: Phacoemulsification done on glaucomatous eyes results in lowering of IOP, and hence the dosage of glaucoma drugs over the long term can be simplified or even discontinued.